'Fresh variants and formulations frozen': Structural features of commercial signs in Oman. (15th July 2014) - Buckingham, Louisa
Abstract : This study analyses structural features of English on commercial signs on shop frontages throughout Oman. The study identifies frequently used structural features which appear to be undergoing a process of nativization (Schneider 2003) within the context of this text type. These include word class flexibility, the extensive use of the gerund at the end of noun phrases and the use of multiple verbs to itemize discrete activities. In some cases, features appear to serve the functions of economizing, or heightening the prominence or degree of explicitness of content; in other cases, structural features revealed the influence of Arabic. Limited evidence was also found for features previously identified in other lingua franca contexts such as the genitive structure with inanimate nouns and plural uncountable nouns.